Histologic and apoptotic changes induced by titanium dioxide nanoparticles in the livers of rats - Alarifi S (Dove Medical Press, 2013)
Saud Alarifi,1 Daoud Ali,1 Amin A Al-Doaiss,1,2 Bahy A Ali,1,3 Mukhtar Ahmed,1 Abdulaziz A Al-Khedhairy11Department of Zoology, College of Science, King Saud University, Riyadh, Saudi Arabia; 2Anatomy and Histology Department, Faculty of Medicine, Sana'a University, Sana'a, Republic of Yemen; 3Genetic Engineering and Biotechnology Research Institute, City for Scientific Research and Technology Applications, Alexandria, EgyptAbstract: Titanium dioxide (TiO2) nanoparticles are among the top five nanoparticles used in consumer products, paints, and pharmaceutical preparations. Given that exposure to such nanoparticles is mainly via the skin and inhalation, the present study was conducted in male Wistar albino rats (Rattus norvegicus). Our aim was to investigate the effect of TiO2 nanoparticles on hepatic tissue in an attempt to understand their toxicity and the potential effect of their therapeutic and diagnostic use. To investigate the effects of TiO2 nanoparticles on liver tissue, 30 healthy male Wistar albino rats were exposed to TiO2 nanoparticles at doses of 63 mg, 126 mg, and 252 mg per animal for 24 and 48 hours. Serum glutamate oxaloacetate transaminase and alkaline phosphatase activity was altered. Changes in hepatocytes can be summarized as hydropic degeneration, cloudy swelling, fatty degeneration, portal and lobular infiltration by chronic inflammatory cells, and congested dilated central veins. The histologic alterations observed might be an indication of hepatocyte injury due to the toxicity of TiO2 nanoparticles, resulting in an inability to deal with accumulated residues from the metabolic and structural disturbances caused by these nanoparticles. The appearance of cytoplasmic degeneration and destruction of nuclei in hepatocytes suggests that TiO2 nanoparticles interact with proteins and enzymes in hepatic tissue, interfering with antioxidant defense mechanisms and leading to generation of reactive oxygen species which, in turn, may induce stress in hepatocytes, promoting atrophy, apoptosis, and necrosis. More immunohistochemical and ultrastructural investigations are needed in relation to TiO2 nanoparticles and their potential effects when used as therapeutic and diagnostic tools.Keywords: TiO2 nanoparticles, rats, liver, histology, TUNEL assay, alkaline phosphatase, apoptosis